Horizontal shortening of the lower eyelid margin in facial nerve palsy - Jamison, Aaron; Patel, Bhupendra C. K.; Malhotra, Raman (Eye (London), 2024)
Background/Objectives To determine whether horizontal lower eyelid margin length shortens following facial nerve palsy (FNP). Subjects/Methods A single-centre retrospective audit of lower eyelid margin horizontal length, measuring from the lower lacrimal punctum to lateral canthal angle with a straight plastic ruler, with the eyelid on gentle stretch (‘punctum-to-canthus (PC) distance’), recorded in all FNP patients reviewed in July–September 2021. Affected and fellow eyes were compared using parametric testing. Results Forty-one patients were reviewed. Seventeen were excluded due to previous surgery that would lengthen (e.g., periosteal flap) or shorten (e.g., lateral tarsal strip) the lower eyelid margin. Of the remaining 24, mean age was 52.5 years (range, 27–79) and 54% were female. Mean PC distance was significantly shorter in affected eyes (26.0 mm, range: 22–34 mm) compared to fellow eyes (27.5 mm, 24–35 mm) (paired t -test, T (23) = 6.06, p < 0.00001). Mean difference between both eyes’ PC distance was 1.5 mm (0–4 mm). Only three patients were still in the ‘paralytic phase’ (i.e., <1 year since FNP onset), and difference in PC distance was 0 mm in all three. A reduction in lower eyelid PC distance was weakly associated with a reduction in upper eyelid lid-margin-to-brow distance ( R = 0.4775, p = 0.0286). Conclusions The lower eyelid margin appears to shorten horizontally following FNP. This study provides proof-of-concept for the use of measuring PC distance in patients with FNP as an additional tool for the overall assessment of soft tissue contraction following FNP. It may help identify patients in whom further lower eyelid margin shortening should be avoided and in whom eyelid lengthening may be required.